Vacuolar sucrose homeostasis is critical for plant development, seed properties, and night-time survival in Arabidopsis. (30th April 2020) - Vu, Duc Phuong; Martins Rodrigues, Cristina; Jung, Benjamin; Meissner, Garvin; Klemens, Patrick A W; Holtgräwe, Daniela; Fürtauer, Lisa; Nägele, Thomas; Nieberl, Petra; Pommerrenig, Benjamin; Neuhaus, H Ekkehard
Abstract : High invertase activity limits vacuolar sucrose accumulation, and a disturbance in vacuolar sucrose homeostasis impairs germination, plant development, seed properties, and night-time survival in Arabidopsis. Abstract: Most cellular sucrose is present in the cytosol and vacuoles of plant cells; however, little is known about the effect of this sucrose compartmentation on plant properties. Here, we examined the effects of altered intracellular sucrose compartmentation in Arabidopsis thaliana leaves by heterologously expressing the sugar beet ( Beta vulgaris ) vacuolar sucrose loader Bv TST2.1 and by generating lines with reduced vacuolar invertase activity ( amiR vi1-2 ). Heterologous expression of BvTST2.1 led to increased monosaccharide levels in leaves, whereas sucrose levels remained constant, indicating that vacuolar invertase activity in mesophyll vacuoles exceeds sucrose uptake. This notion was supported by analysis of tobacco ( Nicotiana benthamiana ) leaves transiently expressing Bv TST2.1 and the invertase inhibitor Nb VIF. However, sucrose levels were strongly elevated in leaf extracts from amiR vi1-2 lines, and experiments confirmed that sucrose accumulated in the corresponding vacuoles. The amiR vi1-2 lines exhibited impaired early development and reduced seed weight. When germinated in the dark, amiR vi1-2 seedlings were less able to convert sucrose into monosaccharides than the wild type. Cold temperatures strongly down-regulated both VI genes, but the amiR vi1-2 lines showed normal frost tolerance. These observations indicate that increased vacuolar sucrose levels fully compensate for the effects of low monosaccharide concentrations on frost tolerance.